Multimedia Learning Introduction to Animal Development in Primary School Students Using Adobe Flash Cs 3(Multimedia Pembelajaran Pengenalan Perkembangan Hewan Pada Siswa Sekolah Dasar Menggunakan Adobe Flash Cs 3) - Irzal Arief Wisky; Riki Iskandar; Dinul Akhiyar (Universitas Putra Indonesia YPTK Padang, 2020)
The media is one of the factors that also determines the success of teaching because it helps students and teachers deliver the subject matter in connection with the teaching objectives. In this condition the use of instructional media in the form of multimedia can improve the efficiency of the process and the quality of teaching and learning outcomes. the use of media in the teaching and learning process can arouse new desires and interests, generate motivation and stimuli for learning. In dealing with students who can be said to not be able to motivate themselves, this becomes a challenge for a teacher. So that the application of multimedia applications can help students in learning, training and directing students in primary schools in the introduction of animal development.